The Use of Virtual Reality Technology in Learning Islamic History - Iis Suryantini; Asep Nursobah; Mamang Subagja; Imas Masripah; Rivan Widiana (International Journal of Education and Digital Learning (IJEDL), 2024)
This research explores the use of Virtual Reality (VR) technology as a tool in learning Islamic history. The main purpose of this study is to evaluate the effectiveness of VR in increasing students' understanding and engagement with Islamic history materials. The research method used is a case study with a qualitative approach, involving observation and documentation. The results show that the use of VR significantly increases students' interest and makes it easier to understand complex historical concepts. Students report that VR experiences allow them to experience firsthand historical context, making them more engaging and memorable. However, the study also identified some challenges, such as technological limitations and the need for specialized training for teachers. These findings demonstrate the potential of VR as an innovation in Islamic history education and offer recommendations for wider implementation